Assessing Climate-Smart Agriculture Adoption: Enhancing Rice Production Resilience in South Sumatra, Indonesia - Wandayantolis; Budianta, Dedik; Yakup; Gunawan, Dodo (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2024)
This study investigates the adoption of Climate-Smart Agriculture (CSA) practices among predominantly traditional rice farmers in South Sumatra, Indonesia, and proposes strategies for enhancing resilience to climate variability. A total of 98 farmers across nine districts participated in structured surveys and in-depth interviews. The results showed a reliance on modern machinery for land preparation (62.8%) alongside a considerable use of traditional tools (26.5%). High awareness of climate change (87.9%) and its impacts, along with a substantial understanding of the negative effects of chemical fertilizers (67.7%), were observed. The use of weather forecasts by 34.7% of respondents highlighted the importance of reliable climate information in agricultural decision-making. Adaptive practices for drier conditions include water management (40%) and crop management methods (25%), while improved drainage (40%) and other flood prevention measures (35%) were commonly adopted for wetter conditions. Despite these efforts, 50% of farmers reported decreased productivity during dry seasons due to the significant impact of irregular rainfall, while approximately 42% managed to increase productivity during wetter conditions through adaptive practices. To enhance CSA adoption, continuous education and awareness programs, promoting energy-efficient machinery and organic farming methods, and improving access to accurate weather forecasts are recommended. The development of resilient crop varieties and the provision of financial and technical support are also essential. Implementing these strategies can facilitate the integration of CSA into the farming system, ensuring a resilient and sustainable agricultural sector in South Sumatra that supports both productivity and environmental preservation, contributing to long-term food security and sustainable development in the region.